Moral Education in Building Superior Character in an Ethical Society - Rizki Bahari (al-Afkar, Journal For Islamic Studies, 2025)
Moral education is an important aspect in the formation of ethical individual and societal character. This article aims to explain the importance of moral education in building superior character, as well as providing several strategies that can be applied in the context of ethical community moral education. This study uses a qualitative approach with the library research method. Library research is a type of qualitative research method carried out by using literature in the form of books, journals, notes, and research reports from previous studies. There are several important aspects of moral education for society, including; Building Superior Character, Instilling moral values, and forming positive traits. Meanwhile, strategies in moral education include; value-based learning, the role of models and role models, and experience-based learning.